Developing a model of academic achievement of distance education students based on parents' academic involvement with the mediating role of task value, students' sense of belonging to the university, and academic effort - taher mahboobi; Mohammad Bagher Akbarpour Zangalani (Payame Noor University, 2024)
The purpose of this research was to provide a model for predicting academic achievement of distance education students based on parental academic involvement with the mediating role of task value, students' sense of belonging to the university, and academic effort. The study sample was 300 undergraduate students of Payam Noor University in Khoy Center in the academic year 2002-2013, who were selected by stratified random sampling. The data collection tool was a questionnaire consisting of the task value subscale (Pintrich et al., 1991), sense of belonging (Wang, White, and Eccles, 2011), academic effort (Dupirat and Marin, 2005), and parental academic involvement subscale. Academic achievement was also measured by inserting a question about students' academic averages through self-reporting. Advanced correlation schemes (path analysis) were used for data analysis. The results of the research generally showed that the relationship between parents' academic involvement and the academic achievement of distance education students is influenced by the dimensions of emotional and behavioral academic engagement. In such a way the direct effect of parents' academic involvement on students' academic achievement was not confirmed, but parental academic involvement showed a positive indirect effect on academic achievement through the students' sense of belonging to the university, the value of the task, and academic effort. In addition, concerning the direct effect of research variables on academic achievement, the most positive effect was related to academic effort. Also,